Ang sabi ni nanay, and sabi ni tatay - Calagopi, Sacha; Bauza, jamie; San Buenaventura, Janina (Makati City UNICEF, 2015)
"Mother teaches Rosalie to clean, go to amrket, and to laundry. Meanwhile, father trains Francis to do minor repairs and wash the car."--Page 4 of cover.
"Unite for children."
Unang limbag ng unang edisyon, 2002
"Recommended for children ages 3 and above."
"In English & Filipino text!"
Keywords: Children's stories, Philippine (English)